2018
DOI: 10.1158/1078-0432.ccr-17-1912
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Response in a Triple-Negative Breast Cancer Cohort Treated with Neoadjuvant Carboplatin and Docetaxel According to Lehmann's Refined Classification

Abstract: Triple-negative breast cancer (TNBC) requires the iden- tification of reliable predictors of response to neoadjuvant chemotherapy (NACT). For this purpose, we aimed to evaluate the performance of the TNBCtype-4 classifier in a cohort of patients with TNBC treated with neoadjuvant carboplatin and docetaxel (TCb). Patients with TNBC were accrued in a nonrandomized trial of neoadjuvant carboplatin AUC 6 and docetaxel 75 mg/m for six cycles. Response was evaluated in terms of pathologic complete response (pCR, ypT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 38 publications
5
66
0
1
Order By: Relevance
“…In the present analysis, basal‐like subtype was associated with a higher pCR rate compared to other subtypes in all patients, but the relative advantage associated with basal‐like subtype occurred in both arms (gem‐ and carbo‐containing). This result is consistent with previous findings indicating that basal‐like phenotype could be associated with higher chemosensitivity for a broader range of CHT regimens, for example, A/T‐containing NACT, carbo‐taxane or gem‐taxane based combinations . Although other trials using intensive polychemotherapy with/or without bevacizumab did not show any predictive effect of basal‐like subtype regarding pCR, our data support further research on a deescalated CHT approach focusing preferentially on patients with basal‐like subtype.…”
Section: Discussionsupporting
confidence: 92%
“…In the present analysis, basal‐like subtype was associated with a higher pCR rate compared to other subtypes in all patients, but the relative advantage associated with basal‐like subtype occurred in both arms (gem‐ and carbo‐containing). This result is consistent with previous findings indicating that basal‐like phenotype could be associated with higher chemosensitivity for a broader range of CHT regimens, for example, A/T‐containing NACT, carbo‐taxane or gem‐taxane based combinations . Although other trials using intensive polychemotherapy with/or without bevacizumab did not show any predictive effect of basal‐like subtype regarding pCR, our data support further research on a deescalated CHT approach focusing preferentially on patients with basal‐like subtype.…”
Section: Discussionsupporting
confidence: 92%
“…A combined analysis of four datasets however showed that Basal-like one tumours had a significantly higher response rate compared to the other subtypes. Similar results were also found in a recent study by Echavarria et al [13] in which RNA sequencing data from FFPE samples was available for 94 patients treated with neoadjuvant carboplatin and docetaxel. Pathological complete response rates were significantly associated with the refined Lehmann subtypes (p = 0.027) with the highest rate seen in Basal-1 patients with 65.6%, followed by 47.4% in Basal-2, 34.8% in Mesenchymal, and 21.4% in Luminal androgen receptor (AR) [13].…”
Section: -30% Highsupporting
confidence: 89%
“…This led to a revised classification, TNBC-type4, into four stable transcriptional subtypes (BL1, BL2, M, and LAR) that significantly differ not only in prognosis and response to chemotherapy, but also in initial presentation and patterns of recurrence, where regional nodal involvement is more common in LAR TNBC and metastatic recurrences have tropism to the lung in M subtypes and to the bone in LAR subtypes. Similar to the seven-subtype classification, response to neoadjuvant chemotherapy (platinum-and taxane-based regimen) is significantly associated with TNBCtype4 subtypes (P = 0.027), with the highest and lowest pCR rates reported in BL1 (65.6%) and LAR (21.4%), respectively (19). These findings highlight a major limitation of classifiers defined based on the profiling of bulk tumors that cannot distinguish between tumor and stromal cells and support the increasing use of single-cell techniques to improve the characterization of the tumor and its microenvironment.…”
Section: Molecular Definition Of Tnbc Heterogeneitymentioning
confidence: 67%